PENERAPAN LAYANAN BIMBINGAN KELOMPOK DENGAN PENDEKATAN TRAIT AND FACTOR UNTUK MEMBERIKAN PEMAHAMAN TENTANG KARIR PESERTA DIDIK KELAS XI TKJ - nelmayenti nelmayenti (LP3M STKIP Muhammadiyah Muara Bungo, 2021)
The main purpose of implementing group guidance services with the Trait and Factor approach is to provide students with an understanding of careers due to the lack of information obtained by students about careers so that future career planning and selection are in accordance with the potential of the individual. This study aims to determine the implementation of the approach through group guidance for students who do not get and know information about careers in class XI TKJ SMK Negeri 1 Bungo in the 2019/2020 Academic Year. This research is a qualitative research. The subjects in this study were 5 students of class XI TKJ 1 and 5 students of class XI TKJ 2. Data collection techniques in this study were using observation and interviews. The data analysis technique for the implementation of the research was carried out by means of data reduction, data presentation and conclusions during the study. So from these results it can be seen that the increase in students' knowledge of understanding about careers and career selection and planning for the future. Thus the application of group guidance services with a trait and factor approach to provide an understanding of the careers of class XI TKJ SMK Negeri 1 Bungo Academic Year 2019/2020 can increase understanding of careers.